Developing Students’ Critical Thinking Skills through Contextual Case-Based Learning: A Quasi-Experimental Study - Sirajudin, Nuraini; Suratno, Joko; Sahjat, Sumarni (Jurnal Pendidikan MIPA, 2025)
Rarely was there a learning exercise that could reliably enhance critical thinking abilities in the classroom.  Consequently, a different approach was required to address the issue.  Contextual Case-Based Learning (CCBL) is an alternative learning activity that could be utilized as a tool to enhance the fundamental abilities required in this century.  It was proposed that 21st-century learning incorporate CCBL.   This study aimed to investigate the impact of the learning model in helping students develop their critical thinking skills.  This study employed a posttest-only design with non-equivalent groups, utilizing a quasi-experimental approach. The total sample class is 44 pre-service biology teachers. There were 22 students in the traditional class and 22 students in the Contextual Case-Based Learning (CCBL) session.  Students in the CCBL class had an average critical thinking score of 53.64, with a standard deviation of 19,160.  However, in the conventional classroom, pupils' critical thinking scores averaged 36.82 with a standard deviation of 18,358.  The standard deviation was 20,402, and the average for both groups was 45.23. Moreover, the learning approach factor has a p-value of less than 0.05, as determined by a two-way ANOVA.  It suggests that learning strategies have a significant impact on students' ability to think critically.  The p-value for the factor of students' prior critical thinking skill levels is less than 0.05.  This suggests that students' earlier critical thinking abilities have a statistically significant impact of 5% on their subsequent critical thinking abilities.  A p-value greater than 0.05 was found for the interaction between the model learning elements and the students' pre-existing critical thinking skills.  Therefore, it follows that the two elements taken together do not affect pupils' capacity for critical thinking. Students' critical thinking skills ranged from poor to moderate, and their responses to the test's questions were generally below average.      Keywords: contextual case-based learning; critical thinking skills.